2009
DOI: 10.1007/s10577-009-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide approaches to determining origin distribution

Abstract: Genome integrity depends upon a highly co-ordinated process that ensures the exact duplication of the genome at each cell cycle. Genomic mapping of DNA replication starting points in mammals, known as origins of replication, is an important step towards our understanding of how this essential mechanism is regulated throughout complex genomes. Two recent studies carried out in both human and mouse cells have revealed a strong association between replication origins and transcriptional regulatory elements. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In silico analysis of these origins revealed that ∼43% of origins possess E-box element (Supplementary Table S4). However, the regulation of origins by c-Myc occupancy could be under the tight temporal control as evident from ChIP-on-chip data reported recently (44). To further elucidate the molecular underpinnings of temporally programmed c-Myc occupancy, we used methylation-sensitive restriction analysis (MSRA) for the E-box element as it is well known that methylated E-box (mE-box) could not recruit c-Myc.…”
Section: Resultsmentioning
confidence: 84%
“…In silico analysis of these origins revealed that ∼43% of origins possess E-box element (Supplementary Table S4). However, the regulation of origins by c-Myc occupancy could be under the tight temporal control as evident from ChIP-on-chip data reported recently (44). To further elucidate the molecular underpinnings of temporally programmed c-Myc occupancy, we used methylation-sensitive restriction analysis (MSRA) for the E-box element as it is well known that methylated E-box (mE-box) could not recruit c-Myc.…”
Section: Resultsmentioning
confidence: 84%
“…Although the CHO DHFR locus is one of the most well-studied initiation zones, different results have provided different interpretations of the frequency with which replication initiates at different sites within the zone, often referred to as ‘origin efficiency’ (30,42). The most direct means to evaluate origin efficiency is by examining the location and frequency of initiation sites on individual DNA fibers, and this method has not been applied to study initiation at the CHO DHFR locus.…”
Section: Resultsmentioning
confidence: 99%
“…These short (80-120 bp) origins of replication contain an essential, conserved element called the ARS consensus sequence (ACS) that is bound by the eukaryotic initiator, the origin recognition complex (ORC, Bell and Dutta, 2002). With the exception of some embryonic tissues, the initiation of replication in metazoan organisms also occurs at reproducible positions, however, no consensus sequence is associated with these sites (Cadoret and Prioleau, 2010). Although in vitro assays for the initial helicase loading event at a defined origin exist (Remus and Diffley, 2009), the loaded helicases are inactive and assays for their activation and for origin-dependent replication initiation have not been described.…”
Section: Introductionmentioning
confidence: 99%